Receipt of National Comprehensive Cancer Network guideline‐concordant prostate cancer care among African American and Caucasian American men in North Carolina. Issue 12 (10th April 2013) - Ellis, Shellie D.; Blackard, Bonny; Carpenter, William R.; Mishel, Merle; Chen, Ronald C.; Godley, Paul A.; Mohler, James L.; Bensen, Jeannette T.
<x xml:space="preserve">Abstract</x> BACKGROUND African Americans have a higher incidence of prostate cancer and experience poorer outcomes compared with Caucasian Americans. Racial differences in care are well documented; however, few studies have characterized patients based on their prostate cancer risk category, which is required to differentiate appropriate from inappropriate guideline application. METHODS The medical records of a population‐based sample of 777 North Carolina men with newly diagnosed prostate cancer were studied to assess the association among patient race, clinical factors, and National Comprehensive Cancer Network (NCCN) guideline‐concordant prostate cancer care. RESULTS African Americans presented with significantly higher Gleason scores (P = .025) and prostate‐specific antigen levels (P = .008) than did Caucasian Americans. However, when clinical T stage was considered as well, difference in overall risk category only approached statistical significance (P = .055). Across risk categories, African Americans were less likely to have surgery (58.1% versus 68.0%, P = .004) and more likely to have radiation (39.0% versus 27.4%, P = .001) compared with Caucasian Americans. However, 83.5% of men received guideline‐concordant care within 1 year of diagnosis, which did not differ by race in multivariable analysis (odds ratio = 0.83; 95% confidence interval = 0.54‐1.25). Greater patient‐perceived access to care was associated with greater odds of receiving guideline‐concordant care (odds ratio = 1.06; 95% confidence interval = 1.01‐1.12). CONCLUSIONS After controlling for NCCN risk category, there were no racial differences in receipt of guideline‐concordant care. Efforts to improve prostate cancer treatment outcomes should focus on improving access to the health care system. Cancer 2013;2282–2290. © 2013 American Cancer Society.